Exploring relationships between personality and anatomy performance. Issue 6 (24th February 2015) - Finn, Gabrielle M.; Walker, Simon J.; Carter, Madeline; Cox, David R.; Hewitson, Ruth; Smith, Claire F.
Abstract : There is increasing recognition in medicine of the importance of noncognitive factors, including personality, for performance, and for good medical practice. The personality domain of conscientiousness is a well‐established predictor of performance in workplace and academic settings. This study investigates the relationships between the "Big Five" personality domains, the facets of conscientiousness and performance in a practical anatomy examination. First‐ and second‐year undergraduate medical students ( n  = 85) completed a paper‐based questionnaire, which included a 50‐item measure of the Big Five personality domains (neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness) and a 60‐item measure of the six conscientiousness facets (orderliness, dutifulness, achievement‐striving, self‐discipline, self‐efficacy, and cautiousness) from the International Personality Item Pool (IPIP). In addition, routinely‐collected academic performance scores from the end of semester anatomy practical examinations (spotters) were obtained. Anatomy examination performance correlated moderately with conscientiousness ( r  = 0.24, P  = 0.03). Of the six facets of conscientiousness, a positive relationship was observed between anatomy examination performance and achievement striving ( r  = 0.22, P  = 0.05). In conclusion, this study found that performance in an anatomy examination was related to higher levels of conscientiousness and, more specifically, to higher levels of achievement striving. The results have implications for selection and assessment in medicine. Anat Sci Educ 8: 547–554. © 2015 American Association of Anatomists.